IMPROVING THE QUALITY AND EFFICIENCY OF MANAGING PRESCHOOL EDUCATION INSTITUTIONS BASED ON A CORPORATE APPROACH - Rayimkulov Akmal (American Journals, 2025)
This article examines the main approaches to implementing the principles of the corporate approach in enhancing the effectiveness and quality of management in preschool education institutions. It proposes ways to improve management efficiency through effective resource utilization, strategic planning, key performance indicators (KPIs), and innovation based on collaboration.
Keywords: Strategy of action, concept, Law